Sonography opportunities in differential diagnosis and simple proiferating corporal uterine fibroids - A. V. Babkina; V. A. Krutova; N. V. Naumova (Кубанский научный медицинский вестник, 2014)
Depending on the nature of proliferative processes morphological forms isolated uterine fibroids: a simple and proliferating. Based on the study results of the morphological structure of fibroids received in the surgical treatment of patients of reproductive age was a retrospective analysis of sonographic parameters. Identifies parameters with the greatest diagnostic and prognostic value. Based on the data obtained mathematical model was developed that allows high sensitivity and specificity to determine the morphological type of uterine fibroids. That has been proven in a prospective study.